Camino ghosts - Grisham, John (Grisham, John. Camino series, 2024)
On Camino Island, popular bookseller Bruce Cable tells Mercer Mann an irresistible tale that might be her next novel. A giant resort developer is using its political muscle and deep pockets to claim ownership of a deserted island between Florida and Georgia. Only the last living inhabitant of the island, Lovely Jackson, stands in its way. What the developer doesn't know is that the island has a remarkable history, and locals believe it is cursed... and the past is never the past..."--